Use of mitomycin c versus gentamicin and dexamethasone in endonasal endoscopic dacrocystorhinostomy - Buche, Aniket R.; Garud, Sachin H.; Gawarle, Surendra H.; Chamania, Gaurav A. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: Dacrocystorhinostomy (DCR) is the procedure done to drain the lacrimal sac in cases of nasolacrimal duct obstruction or in chronic dacrocystitis. New advancements in nasal endoscopic surgeries have given results comparable to external DCR. This is a prospective, case control, randomized, double blinded study to compare efficacy of mitomycin c local application versus gentamicin + dexamethasone local application intraoperatively. Methods: Fifty two patients who underwent endonasal endoscopic DCR at our Tertiary care centre between October 2015 and February 2017. All patients were operated by a single surgeon with double blind method of assigning case. In 26 patients pledgets soaked with 0.4 mg/ml mitomycin C were kept over operative site for 10 min and in other 26 patients pledgets soaked with gentamicin and dexamethasone. Post operatively patients were assessed after 1st and 2nd week and 1st and 3rd month after surgery; post-operative complaints of epiphora were graded. Results: Maximum patients belonged to the age group of 31-60 yrs (78%), females constituted the majority with n=36 (69%). At the end of the study Group A had 92% success and Group B had 85% relief in complaints. Conclusions: We have found statistically insignificant difference between the outcome of local application of Mitomycin C and Gentamicin and dexamethasone. Thus it can be used as substitute or adjuvant with mitomycin C in the intraoperative procedure.